A meta-analysis of the benefits of mindfulness-based stress reduction (MBSR) on psychological function among breast cancer (BC) survivors - Huang, Hua-ping; He, Mei; Wang, Hai-yan; Zhou, Mengjun (Breast cancer (Tokyo, Japan), 2016)
Background Psychological issue is the most common co-morbidity of women with breast cancer (BC) after receiving treatment. Effective coping with this problem is significant importance. The aim of this meta-analysis is to evaluate the benefits of mindfulness-based stress reduction (MBSR) on psychological distress among breast cancer survivors. Methods PUBMED, EMBASE, and the Cochrane Central Register of Controlled Trials were systematically searched from their inception to June 30, 2014. Two reviewers independently reviewed and extracted the data. The primary outcomes of interest were psychological domains. Review Manager 5.3 was used to pool collected data. Results Nine articles involving 964 participants were identified. Compared with those in control group, patients in MBSR group have a significant improvement on psychological domains: depression [mean difference (MD), 5.09; 95 % confidence interval (CI), 3.63–6.55; P < 0.00001], anxiety (MD, 2.79; 95 % CI, 1.62–3.96; P < 0.00001), stress (MD, 4.10; 95 % CI, 2.46–5.74; P < 0.00001). MBSR can also improve the overall quality of life (QOL) (MD, −1.16; 95 % CI, −2.21 to −0.12; P = 0.03). Conclusions On the basis of our findings, MBSR shows a positive effect on psychological function and QOL of breast cancer survivors. This approach can be recommended to breast cancer patients as a part of their rehabilitation.